2021
DOI: 10.1002/cav.2029
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of postural interactions between users and a listening virtual agent during a simulated job interview

Abstract: Postural interaction is of major importance during job interviews. While several prototypes enable users to rehearse for public speaking tasks and job interviews, few of these prototypes support subtle bodily interactions between the user and a virtual agent playing the role of an interviewer. The design of our system is informed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
(136 reference statements)
0
9
0
Order By: Relevance
“…In a study by Nunamaker et al ( 2011 ), the male agent was perceived as more powerful, whereas the female agent was perceived as more likable. Even when male and female agents wore the same clothes, exhibited the same verbal and non-verbal behaviors, and had their faces blurred (thus lacking salient indicators of gender), the female agent was rated higher for warmth than the male agent; however, they were rated similarly for dominance, a trait typically associated with men (Antonio Gómez-Jáuregui et al, 2021 ). In contrast, Kulms et al ( 2011 ), found in their main experiment that participants did not ascribe more masculine traits to the male agents nor more feminine traits to the female agents, unlike in their pretest with 14 participants using still pictures of the same virtual agents.…”
Section: Systematic Review Of Virtual Agents' Gender and Its Impact O...mentioning
confidence: 99%
“…In a study by Nunamaker et al ( 2011 ), the male agent was perceived as more powerful, whereas the female agent was perceived as more likable. Even when male and female agents wore the same clothes, exhibited the same verbal and non-verbal behaviors, and had their faces blurred (thus lacking salient indicators of gender), the female agent was rated higher for warmth than the male agent; however, they were rated similarly for dominance, a trait typically associated with men (Antonio Gómez-Jáuregui et al, 2021 ). In contrast, Kulms et al ( 2011 ), found in their main experiment that participants did not ascribe more masculine traits to the male agents nor more feminine traits to the female agents, unlike in their pretest with 14 participants using still pictures of the same virtual agents.…”
Section: Systematic Review Of Virtual Agents' Gender and Its Impact O...mentioning
confidence: 99%
“…Another reason could be that the avatar visualisation was too far from human-likeness, and therefore the participants had a harder time believing that it was a human that was moving. Listening behaviour is not only dependent on full-body motion, but it is also often combined with verbal feedback [38].…”
Section: Discussionmentioning
confidence: 99%
“…Poppe et al [37] developed rule-based strategies for generating listening behaviour based on the speaker's speech and gaze, including vocal back channelling. A similar approach in terms of selecting new listening behaviours and sequences can be found in [38]. They used a multi-modal corpus of interviews to generate listening behaviour in a virtual agent conducting interviews.…”
Section: Listening Behaviourmentioning
confidence: 99%
“…Similarly, according to, [39], [46], [61] there is a segment of users who use these bots in Processes for personal assistance for various reasons. It was also found in [20], [28], [32], [33], [36], [38], [58], [59], [63], that chatbots are used in customer service processes. In this analysis, the application of chatbots in incident management processes has not been identified; however, it has been mentioned that the teaching process (student-delivered course), customer service process (customer-supplier), health process (patient-doctor), processes for personal assistance (assisted-assistant) and even the training of bots (trained-trainer), are carried out by conversational bots; in the case of the Incident Management Process (user-technician), its application is highly necessary and important to increase productivity in this process.…”
Section: Recent Work On the Types Of Conversational Chatbots That Existmentioning
confidence: 99%
“…In this analysis, the application of chatbots in incident management processes has not been identified; however, it has been mentioned that the teaching process (student-delivered course), customer service process (customer-supplier), health process (patient-doctor), processes for personal assistance (assisted-assistant) and even the training of bots (trained-trainer), are carried out by conversational bots; in the case of the Incident Management Process (user-technician), its application is highly necessary and important to increase productivity in this process. [37], [46]- [48], [53], [54], [59], [65] 3 Customer service processes 9 [23], [31], [35], [36], [39], [41], [61], [62], [66] 4 Health processes 11 [24], [25], [28], [29], [32]- [34], [43], [44], [56], [57] 5 Processes for personal assistance 3 [42], [49], […”
Section: Recent Work On the Types Of Conversational Chatbots That Existmentioning
confidence: 99%